Differentiating mathematical mindset, growth mindset, and self-efficacy through intervention research: a neuroplasticity approach - Xu, Xiaoyu; Dieckmann, Jack A. (Frontiers in Psychology, 2025)
Mathematical Mindset (MM), Growth Mindset (GM), and Self-Efficacy (SE) are critical psychological constructs that shape students' mathematical achievement by influencing cognitive flexibility, problem-solving strategies, and motivational persistence. This study, based on data derived from Xu et al., extends prior research by examining the distinct contributions of MM, GM, and SE in response to an intervention among university students. To better understand how neuroplasticity, MM, and GM manifest in this study, thematic analysis was applied to qualitative interview data, providing deeper insights into the cognitive and behavioral changes induced by the intervention. Using a mixed-methods approach, we analyze quantitative data through correlation heatmaps, contour plots, and scatter visualizations, alongside qualitative data, to provide a comprehensive understanding of how these constructs interact. Findings reveal that MM and SE exhibit a synergistic relationship, where higher levels of both correspond to increased academic performance, cognitive adaptability, and engagement in mathematics. GM, while indirectly influencing achievement, primarily enhances perseverance and learning from mistakes, contributing to the reinforcement of MM and SE. Future research should refine the measurement of MM and GM across different learning environments, investigate the transferability of GM across domains, and explore the role of brain activity in optimizing intervention effectiveness.